Health Care System in Sudan: Review and Analysis of Strength, Weakness, Opportunity, and Threats (SWOT Analysis) - Ebrahim Mohammed Abdullah Ebrahim; Luam Ghebrehiwot; Tasneem Abdalgfar; Muhammad Hanafiah Juni (Sudan Journal of Medical Sciences, 2017)
Background: The Republic of the Sudan located in north-east of Africa and is considered to be a lower-middle income country. The country has well established healthcare system with many drawbacks mainly due to economic and managerial reasons followed by prolonged political instability and sanctions. Objective: The aim of this study is to give an insight over the health services system in Sudan and to analyze the strength, weakness, opportunities, and threats (SWOT).